Neutralization of Aesthetic Information Enthropy in Fiction Text due to Functional Rhythm Halting (Proceedings of Southern Federal University. Philology, 2018)
Galina N. Gumovskaya (Moscow, Russian Federation)The article deals with prosaic text rhythm, which is considered a tool organizing the information structure of the text and the key factor of entropy neutralization. Information structure of the text as a semantic unity functioning as the subject of the act of communication acquires a meaningful order in its interaction with the rhythmic organization: the rhythm neutralizes entropy – an internal disorder of the structure and the uncertainty of the logical content of the text. The rhythmic structure of the text can be presented, both in the plane of expression, and in the plane of content. In the former case, the rhythmic system appears in the form of a periodically reproduced number of units located in a linear sequence of both phonetic segmental and supra segmental levels, as well as of the other levels of the text structure. In the latter case, the rhythmic structure is defined by both in-text and text-through relationships. Therefore, we can claim that rhythm as an ordered periodicity of temporal and qualitative types gives additional information to the utterance and is a means of intensifying the informational structure of the fiction text.The top of hierarchically organized information structure of the text – content-conceptual information – is a complex notion, which cannot be reduced to the idea of the work. This is the author’s idea plus his meaningful interpretation. The study of composite rhythm helps to reveal the regularity of the relations between the two types of the text content – the content of thought and the content of form. Due to the ability of language units to generate associative and connotative ties, as well as the ability of sentences in the text to develop meanings due to functional failure of the rhythm, the entropy of the aesthetic-cognitive plane is removed. Revealed are the mechanisms of the formation of meaning nuances contained in the multifaceted informational content of the utterance.Keywords: text, compositional rhythm, assimilative rhythm, dissimilative rhythm, information, informational structure of the text, entropy, form, redundancy of information.DOI 10.23683/1995-0640-2018-1-191-200